2021
DOI: 10.1177/1559827621994499
|View full text |Cite
|
Sign up to set email alerts
|

The Lunch Conference Diet: Fostering Resident Engagement in Culinary Medicine Through a Curriculum Centered on Changes to Provided Conference Food

Abstract: Background. Despite the burden of chronic disease attributable to lifestyle, most internal medicine residents do not receive adequate training in nutrition and nutrition counseling. Methods. We held a culinary medicine workshop in September 2018, followed by didactic sessions throughout the academic year. Changes were made to lunch conference food to more closely follow the Mediterranean diet and to encourage healthy eating. With a modified NUTCOMP (Nutrition Competence Questionnaire) instrument, we assesses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Reasons for excluding articles reviewed as full-text included wrong study design ( n = 13) [ 4 , 12 – 23 ], wrong population ( n = 5) [ 24 28 ], a failure to report any outcome measures ( n = 3) [ 9 , 29 , 30 ], wrong intervention ( n = 3) [ 26 , 31 , 32 ], and five studies were found to be duplicates of an included paper or had used the same data ( n = 5) [ 33 37 ]. Amongst the 24 included studies, there were six qualitative studies [ 38 43 ], four cross-sectional studies [ 34 , 44 46 ]; seven case studies [ 47 – 53 ], and seven mixed-methods study [ 35 , 54 – 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reasons for excluding articles reviewed as full-text included wrong study design ( n = 13) [ 4 , 12 – 23 ], wrong population ( n = 5) [ 24 28 ], a failure to report any outcome measures ( n = 3) [ 9 , 29 , 30 ], wrong intervention ( n = 3) [ 26 , 31 , 32 ], and five studies were found to be duplicates of an included paper or had used the same data ( n = 5) [ 33 37 ]. Amongst the 24 included studies, there were six qualitative studies [ 38 43 ], four cross-sectional studies [ 34 , 44 46 ]; seven case studies [ 47 – 53 ], and seven mixed-methods study [ 35 , 54 – 59 ].…”
Section: Resultsmentioning
confidence: 99%